Traditional Boarding Schools in Dealing with Sharia Economic Development (Case Study at The Sidogiri Islamic Boarding School, Pasuruan, East Java) (Sharia Faculty Islamic Economic Law Study Department, 2024)
This research aims to examine traditional Islamic boarding schools in facing sharia economic developments by focusing the study on the Sidogiri Pasuruan Islamic Boarding School, East Java. The descriptive case study method with a sociological approach was applied in the data collection process. Meanwhile, data analysis was carried out using data reduction steps, data presentation and drawing conclusions. The results of the study found that Traditional Islamic Boarding Schools are able to maintain and produce human resources with trustworthy personalities (trustworthiness) as the main capital in developing human resources in sharia economic and financial institutions. Although there is no special material related to the study of Maliyyah muamalah fiqh. However, Islamic boarding schools have succeeded in capturing the essence of preparing qualified human resources by implementing the values of trust for students contained in the educational curriculum at Islamic boarding schools.